2003
DOI: 10.1556/aagr.51.2003.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability in the F1 and F2 generations of a diallel cross in six-rowed barley (Hordeum vulgare L.)

Abstract: The F1 and F2 progenies of a ten-parent diallel cross (excluding reciprocals) were analysed for the combining ability of quantitative traits in six-rowed barley (Hordeum vulgare L.). significant differences were indicated between the parents, F1s and F2s for all the characters studied. The gca and sca components of variance were significant for all the traits. Both additive and non-additive gene effects were involved in the genetic control of the characters; however, non-additive gene effects were observed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
6
4
0
Order By: Relevance
“…These results indicate the superiority of these crosses in this trait. These results are in general agreement with those reported by Ahmed (1990), Bhatnagar and Sharma (1997), Sharma et al (2003), Mahmoud, Badeaa (2006)…”
Section: Specific Combining Ability Effectssupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicate the superiority of these crosses in this trait. These results are in general agreement with those reported by Ahmed (1990), Bhatnagar and Sharma (1997), Sharma et al (2003), Mahmoud, Badeaa (2006)…”
Section: Specific Combining Ability Effectssupporting
confidence: 93%
“…Data indicated that P 1 was a good combiner for number of grains/spike and 100-grain weight under both conditions; P 2 for grain yield/plant under both conditions, spike length, spikes/plant, number of grains/spike under stress and plant height under Normal ; P 3 for plant height and grain yield/plant under both conditions and number of grains/spike under stress; P 4 for 100-grain weight under both conditions, spikes/plant under stress and plant height under Normal; P 5 for plant height and number of grains/spike under Normal and P 6 for spike length and grain yield/plant under Normal. Similar results were obtained by Ahmed (1990), Singh et al (2002), Sharma et al (2003), Mahmoud, Badeaa (2006), Amer (2010), Amer et al (2011) and Ismaeil (2015).…”
Section: General Combing Ability Effectssupporting
confidence: 84%
“…of spikes/plant, the first cross for no. of grains/plant and the third, the fourth and the fifth crosses for 100-grain weight, which was agreement with the results obtained by Soylu (2002) and Sharma et al, (2003).…”
Section: Estimation Of Type Of Gene Actionsupporting
confidence: 93%
“…On the other hand, it was negative highly significant for days to heading and maturity dates in the second and the fifth crosses; flag leaf area in the fifth cross, in chlorophyll content in all crosses except for the first cross was non-significant. These results are in harmony with those obtained by Sharma et al, (2003), Singh et al, (2002), Eid (2006), El-Sayed (2007) and El-Shawy (2008).…”
Section: Estimation Of Type Of Gene Actionsupporting
confidence: 91%
See 1 more Smart Citation